Integrating pollen and sedimentary DNA refines reconstructions of vegetation change through human settlement: a case study from Lake Waihau, Aotearoa New Zealand - Xun Li; Georgia Thomson-Laing; Marcus J. Vandergoes; Jamie D. Howarth; Susanna A. Wood (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Embracing wicked problems thinking will advance conservation science and practice - Raegan Davis; Tamara Donnelly; Brenna Hynes; Karolyn McGovern; Douglas Strick; Madison Empey; Steven J. Cooke; Andrew Howarth (Biological Conservation, 2026)

Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Perceptions and beliefs of recreational anglers about Murray Cod (Maccullochella peelii) fishing in Victoria, Australia: A path to enhancing education and outreach - Andy J. Danylchuk; Taylor L. Hunt; Lucas P. Griffin; Andrew Howarth; Sascha Clark Danylchuk; Steven J. Cooke; Meaghan L. Guckian (Fisheries Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Late Holocene climate variability and lake productivity change inferred from the remote alpine catchment of Lake Bright, New Zealand - Julian Eschenroeder; Christopher M. Moy; Sebastian Naeher; Marcus J. Vandergoes; Oliver Rach; Dirk Sachse; Rik Tjallingii; Jamie D. Howarth; Adelaine Moody; Xun Li; Claire Shepherd; Elizabeth Kennedy; et al. (Quaternary Science Reviews, 2026)

Proterozoic highly siderophile element enrichment of the Kaapvaal cratonic Archean mantle - Nadine P. Cooper; D. Graham Pearson; Andreas Auer; Tristan Bongartz; Yannick Bussweiler; Mario Fischer-Gödde; Max Hellers; Geoffrey Howarth; Andrew J. Locock; Ambre Luguet; Carsten Münker; Thomas Stachel; et al. (Chemical Geology, 2026)

A multi-event paleoseismic record from the northern Alpine Fault at Marble Hill, Aotearoa New Zealand - R.M. Langridge; J.D. Howarth; G.L. Coffey; P. Villamor; W.F. Ries; U.A. Cochran; M. Sagar; J. La Greca; E.J. Rhodes; S. Saha; J. Dahl (Geomorphology, 2025)

Twelve strategies for realizing the promise of ecopracticology - Steven J. Cooke; Marco Carlotti; Kgosietsile Velempini; Nathan Heavers; Zhifang Wang; Zoe Moula; Qinghe Hou; Andrew Howarth; Meagan Harper; Andrew N. Kadykalo; Yasuhisa Kondo; Yue Che; et al. (Socio-Ecological Practice Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Earthquake-triggered submarine canyon flushing transfers young terrestrial and marine organic carbon into the deep sea - Katherine L Maier; Catherine E Ginnane; Sebastian Naeher; Jocelyn C Turnbull; Scott D Nodder; Jamie Howarth; Sarah J Bury; Robert G Hilton; Jess IT Hillman (Earth and Planetary Science Letters, 2025)

Integrated onshore–offshore paleoseismic records show multiple slip styles on the plate interface, central Hikurangi subduction margin, Aotearoa New Zealand - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Alan R. Orpin; Stephanie E. Tickle; Lorna J. Strachan; Philip Barnes; Sian Camp; Monique Mckeown; Emily Twort (Quaternary Science Reviews, 2024)

Lacustrine mass movements in active tectonic settings: Lake tsunami sources in New Zealand's South Island - Katie E. Hughes; Sean J. Fitzsimons; Jamie D. Howarth (Geomorphology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Non-probabilistic surveys and sampling in the human dimensions of fisheries - Andrew Howarth; Steven J. Cooke; Vivian M. Nguyen; Len M. Hunt (Reviews in Fish Biology and Fisheries, 2024)

Source and parental melts of poikilitic shergottites: Implications for martian magmatism - Evan W. O'Neal; A.M. Ostwald; A. Udry; J. Gross; M. Righter; T.J. Lapen; J. Darling; G.H. Howarth; R. Johnsen; D.R. McQuaig (Geochimica et Cosmochimica Acta, 2024)

Sedimentary ancient DNA reveals the impact of anthropogenic land use disturbance and ecological shifts on fish community structure in small lowland lake - Georgia Thomson-Laing; Jamie D. Howarth; Javier Atalah; Marcus J. Vandergoes; Xun Li; John K. Pearman; Sean Fitzsimons; Chris Moy; Adelaine Moody; Claire Shepherd; Nicholas McKay; Susanna A. Wood (Science of The Total Environment, 2024)

A paleoecological investigation of recent cyanobacterial blooms and their drivers in two contrasting lakes - Caitlin Wheeler; John K. Pearman; Jamie D. Howarth; Marcus J. Vandergoes; Katherine Holt; Steven A. Trewick; Xun Li; Lucy Thompson; Georgia Thomson-Laing; Mailys Picard; Chris Moy; Nicholas P. Mckay; et al. (Harmful Algae, 2024)

Current Trends and Future Directions in Urban Social Prescribing - J. S. Litt; L. Coll-Planas; A. L. Sachs; M. Masó Aguado; M. Howarth (Current Environmental Health Reports, 2023)

Petrology of an apatite-calcite segregationary kimberlite from the Andriesfontein pipe, Kaapvaal craton - Geoffrey H. Howarth; Gelu Costin; Chad J. Peel; Zuko Qashani (Lithos, 2023)

A taxonomy-free diatom eDNA-based technique for assessing lake trophic level using lake sediments - Rose Gregersen; John K. Pearman; Javier Atalah; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Georgia Thomson-Laing; Lucy Thompson; Susanna A. Wood (Journal of Environmental Management, 2023)

Characterizing carotenoids in cyanobacterial cultures – Opportunities and implications for paleolimnological studies - Jonathan Puddick; Sebastian Naeher; John K Pearman; Carrie D Page; Donato Romanazzi; Lena A Schallenberg; Jamie D Howarth; Marcus J Vandergoes; Susanna A Wood (Harmful Algae, 2023)

Major-, trace-element and Sr-Nd-Hf isotope geochemistry of diamondiferous dykes from Tonguma and Koidu, Sierra Leone: Highly micaceous kimberlites formed by assimilation of metasomatised lithospheric mantle rocks - Angus Fitzpayne; Andrea Giuliani; Geoffrey H. Howarth; Bradley J. Peters; Manuela A. Fehr; Roland Maas (Chemical Geology, 2023)

Constraints on martian depleted shergottite volcanism from the petrogenesis of olivine-phyric shergottites NWA 2046 and NWA 4925 - Chad J. Peel; Geoffrey H. Howarth; James M.D. Day; Petrus le Roux; Olivier Alard (Journal of African Earth Sciences, 2023)

It's all in the mud - The use of sediment geochemistry to estimate contemporary water quality in lakes - Sean Waters; Javier Atalah; Lucy Thompson; Georgia Thomson-Laing; John K. Pearman; Jonathan Puddick; Jamie D. Howarth; Lizette Reyes; Marcus J. Vandergoes; Susanna A. Wood (Applied Geochemistry, 2023)

An integrated proximal-distal radiocarbon dating approach provides improved age constraints for a key Holocene tephra isochron - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Colin J.N. Wilson; Stephanie E. Tickle; Jenni L. Hopkins; Jenny A. Dahl (Quaternary Science Reviews, 2023)

Paleo-diatom records reveal ecological change not detected using traditional measures of lake eutrophication - Rose Gregersen; Jamie D. Howarth; Javier Atalah; John K. Pearman; Sean Waters; Xun Li; Marcus J. Vandergoes; Susanna A. Wood (Science of The Total Environment, 2023)

Rapid characterisation of Mars' mantle reservoirs by in situ laser ablation 87Sr/86Sr analysis of shocked feldspar (maskelynite) - Daniel L. Burgin; James M. Scott; Petrus J. le Roux; Geoffrey Howarth; Marshall C. Palmer; Thomas A. Czertowicz; Marianne Negrini; Malcolm R. Reid; Claudine H. Stirling (Geochimica et Cosmochimica Acta, 2023)

Deterministic processes drive national‐scale patterns in lake surface sediment bacteria and eukaryotic assemblage composition - John K. Pearman; Janet Adamson; Georgia Thomson‐Laing; Lucy Thompson; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Susanna A. Wood (Limnology and Oceanography, 2023)
Biological communities within lake surface sediments play a vital role in biogeochemical cycling and ecosystem services. Knowledge on abundance‐occupancy patterns and assembly processes across large spatial scales and over multiple environmental gradients is limited, yet essential to aid in protection and restoration. In the present study, surface sediment samples were collected from 296 lakes across a wide spatial scale and covering multiple interacting environmental gradients including size, depth, altitude, and trophic state. A suite of physicochemical parameters were used to characterize the environmental conditions and bacterial and eukaryotic assemblages were determined using 16S and 18S rRNA metabarcoding. The majority (~ 55%) of amplicon sequence variants were only found in a single lake with eukaryotes having a more restricted distribution than bacteria. Deterministic processes were inferred to be dominant for both bacteria (78%) and eukaryotes (51%), with variable selection being especially important for bacteria (49%). Variation partitioning indicated that land use in the catchment, which is strongly related to trophic state, was the most important environmental factor in explaining the assemblage composition. This nationwide study across broad gradients provides new insights into the ecology of bacteria and eukaryotes in lake surface sediments and a platform to better understand the effects of multiple environmental stressors on lake sediment assemblages.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Lake microbial communities are not resistant or resilient to repeated large‐scale natural pulse disturbances - Katie A. Brasell; Jamie Howarth; John K. Pearman; Sean J. Fitzsimons; Anastasija Zaiko; Xavier Pochon; Marcus J. Vandergoes; Kevin S. Simon; Susanna A. Wood (Molecular Ecology, 2021)
Opportunities to study community‐level responses to extreme natural pulse disturbances in unaltered ecosystems are rare. Lake sediment records that span thousands of years can contain well‐resolved sediment pulses, triggered by earthquakes. These palaeorecords provide a means to study repeated pulse disturbances and processes of resistance (insensitivity to disturbance) and ecological resilience (capacity to regain structure, function and process). In this study, sedimentary DNA was extracted from a sediment core from Lake Paringa (New Zealand) that is situated in a near natural catchment. Metabarcoding and inferred functions were used to assess the lake microbial community over the past 1100 years – a period that included four major earthquakes. Microbial community composition and function differed significantly between highly perturbed (postseismic, ~50 years) phases directly after the earthquakes and more stable (interseismic, ~250 years) phases, indicating a lack of community resistance. Although community structure differed significantly in successive postseismic phases, function did not, suggesting potential functional redundancy. Significant differences in composition and function in successive interseismic phases demonstrate that communities are not resilient to large‐scale natural pulse disturbances. The clear difference in structure and function, and high number of indicator taxa (responsible for driving differences in communities between phases) in the fourth interseismic phase probably represents a regime shift, possibly due to the two‐fold increase in sediment and terrestrial biospheric organic carbon fluxes recorded following the fourth earthquake. Large pulse disturbances that enhance sediment inputs into lake systems may produce an underappreciated mechanism that destabilises lake ecosystem processes.

Population genomics of Mediterranean oat (A. sativa) reveals high genetic diversity and three loci for heading date - F. J. Canales; G. Montilla-Bascón; W. A. Bekele; C. J. Howarth; T. Langdon; N. Rispail; N. A. Tinker; E. Prats (Theoretical and Applied Genetics, 2021)
Key message Genomic analysis of Mediterranean oats reveals high genetic diversity and three loci for adaptation to this environment. This information together with phenotyping and passport data, gathered in an interactive map, will be a vital resource for oat genetic improvement. Abstract During the twentieth century, oat landraces have increasingly been replaced by modern cultivars, resulting in loss of genetic diversity. However, landraces have considerable potential to improve disease and abiotic stress tolerance and may outperform cultivars under low input systems. In this work, we assembled a panel of 669 oat landraces from Mediterranean rim and 40 cultivated oat varieties and performed the first large-scale population genetic analysis of both red and white oat types of Mediterranean origin. We created a public database associated with an interactive map to visualize information for each accession. The oat collection was genotyped with 17,288 single-nucleotide polymorphism (SNP) loci to evaluate population structure and linkage disequilibrium (LD); to perform a genome-wide association study (GWAs) for heading date, a key character closely correlated with performance in this drought-prone area. Population genetic analysis using both structure and PCA distinguished two main groups composed of the red and white oats, respectively. The white oat group was further divided into two subgroups. LD decay was slower within white lines in linkage groups Mrg01, 02, 04, 12, 13, 15, 23, 33, whereas it was slower within red lines in Mrg03, 05, 06, 11, 21, 24, and 28. Association analysis showed several significant markers associated with heading date on linkage group Mrg13 in white oats and on Mrg01 and Mrg08 in red oats.

Deforestation caused abrupt shift in Great Lakes nitrogen cycle - Eric J. Guiry; Michael Buckley; Trevor J. Orchard; Alicia L. Hawkins; Suzanne Needs‐Howarth; Erling Holm; Paul Szpak (Limnology and Oceanography, 2020)
Despite the longstanding significance of North America's Great Lakes, little is known about their preindustrial ecology. Here, we report on when and how humans first became a main driver of Lake Ontario's nutrient dynamics. Nitrogen isotope analyses of archaeological fish show that, prior to the 1830s, Lake Ontario's nitrogen cycle and the trophic ecology of its top predators had remained stable for at least 800 yrs, despite Indigenous and historical European agricultural land management across the region. An abrupt shift in the nitrogen isotope composition of Lake Ontario's fish community is evident in the early to mid‐19 th century and reflects the initiation of industrial‐scale forest clearance. These data show how the nitrogenous nutrient regimes of even the world's largest freshwater ecosystems can be highly sensitive to short‐term watershed forest cover disturbances and indicate a profound shift in the relationship between humans and their environment.

A Heuristic Method for Determining Changes of Source Loads to Comply with Water Quality Limits in Catchments - Alexander H. Elliott; Ton H. Snelder; Richard W. Muirhead; Ross M. Monaghan; Amy L. Whitehead; Santiago A. Bermeo-Alvear; Carl J. Howarth (Environmental Management, 2020)

Spatial and temporal variation in mountain hare (Lepus timidus) abundance in relation to red grouse (Lagopus lagopus scotica) management in Scotland - Nicholas Hesford; Kathy Fletcher; David Howarth; A Adam Smith; Nicholas J. Aebischer; David Baines (European Journal of Wildlife Research, 2019)

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

Dietary inclusions of dried macroalgae meal in formulated diets improve the growth of greenlip abalone (Haliotis laevigata) - Matthew S. Bansemer; Jian G. Qin; James O. Harris; Duong N. Duong; Krishna-Lee Currie; Gordon S. Howarth; David A. J. Stone (Journal of Applied Phycology, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

A hydroclimate-proxy model based on sedimentary facies in an annually laminated sequence from Lake Ohau, South Island, New Zealand - Heidi A. Roop; Richard Levy; Gavin B. Dunbar; Marcus J. Vandergoes; Jamie Howarth; Sean Fitzsimons; Heung Soo Moon; Christian Zammit; Robert Ditchburn; Troy Baisden; Ho Il Yoon (Journal of Paleolimnology, 2016)

Effects of ecosystem protection on scallop populations within a community-led temperate marine reserve - Leigh M. Howarth; Callum M. Roberts; Julie P. Hawkins; Daniel J. Steadman; Bryce D. Beukers-Stewart (Marine Biology, 2015)

Dapagliflozin reduces the amplitude of shortening and Ca2+ transient in ventricular myocytes from streptozotocin-induced diabetic rats - N. N. Hamouda; V. Sydorenko; M. A. Qureshi; J. M. Alkaabi; M. Oz; F. C. Howarth (Molecular and Cellular Biochemistry, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Historical biogeography of the predominantly Australian plant family Goodeniaceae - Rachel S. Jabaily; Kelly A. Shepherd; Andrew G. Gardner; Mats H. G. Gustafsson; Dianella G. Howarth; Timothy J. Motley (Journal of Biogeography, 2014)
Aim The plant family Goodeniaceae includes 12 genera, largely restricted to Australia. They are a diverse and conspicuous element of the country's ecosystems and an important clade to consider in the effort to reconstruct the historical biogeography of this continent. We used a time‐calibrated molecular phylogeny to perform ancestral‐area reconstructions for the family, in order to: (1) determine its area of origin; (2) test whether vicariance played a role in the history of lineages occupying the south‐western and south‐eastern regions; (3) trace diversification processes in the central arid zone; and (4) trace potential eastward dispersals into the Pacific. Location Australia and the Pacific. Methods We employed a previously published molecular dataset to develop a time‐calibrated phylogeny for the Goodeniaceae using beast 1.6.1 with both primary and secondary node calibrations. Ancestral areas were reconstructed via both dispersal–extinction–cladogenesis ( DEC ) and statistical dispersal–vicariance analysis (S‐ DIVA ). Results The Goodeniaceae split from Asteraceae + Calyceraceae c . 78 Ma, with the divergence of the Lechenaultia , Anthotium and Dampiera ( LAD ) clade from the remainder of the family c . 67 Ma. Although the geographical origin of the family is equivocal, the LAD clade originated in south‐western Australia, and the remainder of the family, especially Goodenia s.l., probably originated in the central Eremaean zone. The majority of Goodenia cladogenesis events occurred during the Miocene, with expansions to the north, south‐east and south‐west. The crown radiation of Scaevola s.l. occurred later, during the second half of the Miocene, and has involved several recent extra‐Australian dispersals into the Pacific. Main conclusions Although it is unclear where in Australia the family originated, our results support a south‐western origin for the LAD clade and considerable diversification of some clades within Goodenia s.l. and Scaevola s.l. in that zone. A relative paucity of mid‐Miocene sister relationships between south‐western and south‐eastern lineages suggests that the occupants of these regions were not affected by contemporary vicariance events. Instead, our results suggest that the aridifying Eremaean zone was an important source and sink for lineages, especially in Goodenia s.l. Dispersal is inferred for the extra‐Australian lineages due to their recent origins.

Komsomolskaya diamondiferous eclogites: evidence for oceanic crustal protoliths - John F. Pernet-Fisher; Geoffrey H. Howarth; Yang Liu; Peter H. Barry; Laura Carmody; John W. Valley; Robert J. Bodnar; Zdislav V. Spetsius; Lawrence A. Taylor (Contributions to Mineralogy and Petrology, 2014)

Genetic Diversity and Population Structure Among Oat Cultivars and Landraces - G. Montilla-Bascón; J. Sánchez-Martín; N. Rispail; D. Rubiales; L. Mur; T. Langdon; I. Griffiths; C. Howarth; E. Prats (Plant Molecular Biology Reporter, 2013)

Effects of exercise training on excitation–contraction coupling and related mRNA expression in hearts of Goto-Kakizaki type 2 diabetic rats - K. A. Salem; M. A. Qureshi; V. Sydorenko; K. Parekh; P. Jayaprakash; T. Iqbal; J. Singh; M. Oz; T. E. Adrian; F. C. Howarth (Molecular and Cellular Biochemistry, 2013)

Eddy correlation measurements of oxygen fluxes in permeable sediments exposed to varying current flow and light - Peter Berg; Matthew H. Long; Markus Huettel; Jennie E. Rheuban; Karen J. McGlathery; Robert W. Howarth; Kenneth H. Foreman; Anne E. Giblin; Roxanne Marino (Limnology and Oceanography, 2013)
Based on noninvasive eddy correlation measurements at a marine and a freshwater site, this study documents the control that current flow and light have on sediment‐water oxygen fluxes in permeable sediments. The marine sediment was exposed to tidal‐driven current and light, and the oxygen flux varied from night to day between −29 and 78 mmol m −2 d −1 . A fitting model, assuming a linear increase in oxygen respiration with current flow, and a photosynthesis‐irradiance curve for light‐controlled production reproduced measured fluxes well ( R 2 = 0.992) and revealed a 4‐fold increase in oxygen uptake when current velocity increased from ∼ 0 to 20 cm s −1 . Application of the model to a week‐long measured record of current velocity and light showed that net ecosystem metabolism varied substantially among days, between −27 and 31 mmol m −2 d −1 , due to variations in light and current flow. This variation is likely typical of many shallow‐water systems and highlights the need for long‐term flux integrations to determine system metabolism accurately. At the freshwater river site, the sediment‐water oxygen flux ranged from −360 to 137 mmol m −2 d −1 . A direct comparison during nighttime with concurrent benthic chamber incubations revealed a 4.1 times larger eddy flux than that obtained with chambers. The current velocity during this comparison was 31 cm s −1 , and the large discrepancy was likely caused by poor imitation by the chambers of the natural pore‐water flushing at this high current velocity. These results emphasize the need for more noninvasive oxygen flux measurements in permeable sediments to accurately assess their role in local and global carbon budgets.

Diurnal variation in chlorophyll fluorescence of Thalassia testudinum seedlings in response to controlled salinity and light conditions - Jacqueline F. Howarth; Michael J. Durako (Marine Biology, 2013)

Tidal and Groundwater Fluxes to a Shallow, Microtidal Estuary: Constraining Inputs Through Field Observations and Hydrodynamic Modeling - Neil K. Ganju; Melanie Hayn; Shih-Nan Chen; Robert W. Howarth; Patrick J. Dickhudt; Alfredo L. Aretxabaleta; Roxanne Marino (Estuaries and Coasts, 2012)

Extracting sea level residual in tidally dominated estuarine environments - Jennifer M. Brown; Rodolfo Bolaños; Michael J. Howarth; Alejandro J. Souza (Ocean Dynamics, 2012)

Guest editors' preface: Geoinformatics 2007 - Peng Gong; Philip J. Howarth; Bing Xu; Weimin Ju (International Journal of Remote Sensing, 2010)

Residual circulation and stratification in the Liverpool Bay region of freshwater influence - Florence Verspecht; Tom P. Rippeth; John H. Simpson; Alejandro J. Souza; Hans Burchard; M. John Howarth (Ocean Dynamics, 2009)

Limitations of integrated assessment models of climate change - Frank Ackerman; Stephen J. DeCanio; Richard B. Howarth; Kristen Sheeran (Climatic Change, 2009)

Effects of streptozotocin-induced diabetes on connexin43 mRNA and protein expression in ventricular muscle - F. C. Howarth; N. J. Chandler; S. Kharche; J. O. Tellez; I. D. Greener; T. T. Yamanushi; R. Billeter; M. R. Boyett; H. Zhang; H. Dobrzynski (Molecular and Cellular Biochemistry, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

Mapping an inland wetland complex using hyperspectral imagery - M. Y. Jollineau; P. J. Howarth (International Journal of Remote Sensing, 2008)

Identification of roots in lava tube caves using molecular techniques: implications for conservation of cave arthropod faunas - Francis G. Howarth; Shelley A. James; Wendy McDowell; David J. Preston; Clyde T. Imada (Journal of Insect Conservation, 2007)

Reconciling Carbon-cycle Concepts, Terminology, and Methods - F. S. Chapin; G. M. Woodwell; J. T. Randerson; E. B. Rastetter; G. M. Lovett; D. D. Baldocchi; D. A. Clark; M. E. Harmon; D. S. Schimel; R. Valentini; C. Wirth; J. D. Aber; et al. (Ecosystems, 2006)

Tricarboxylic acid cycle intermediates accumulate at the onset of intense exercise in man but are not essential for the increase in muscle oxygen uptake - Jens Bangsbo; Martin J. Gibala; Krista R. Howarth; Peter Krustrup (Pflügers Archiv - European Journal of Physiology, 2006)

Mechanical Impedance and Nutrient Acquisition in Rice - Donna A. Brown; Lawrence J. Clark; Jonathan R. Howarth; Saroj Parmar; Malcolm J. Hawkesford (Plant and Soil, 2006)

The progressive effects of a fat enriched diet on ventricular myocyte contraction and intracellular Ca2+ in the C57BL/6J mouse - F. C. Howarth; M. A. Qureshi; A. J. Gbewonyo; S. Tariq; E. Adeghate (Molecular and Cellular Biochemistry, 2005)

Voltage-dependence of contraction in streptozotocin-induced diabetic myocytes - N.K. Bracken; A.J. Woodall; F.C. Howarth; J. Singh (Molecular and Cellular Biochemistry, 2004)

Tidal currents, energy flux and bottom boundary layer thickness in the Clyde Sea and North Channel of the Irish Sea - A. M. Davies; P. Hall; M. J. Howarth; P. J. Knight; R. J. Player (Ocean Dynamics, 2004)

Cloning of two contrasting high-affinity sulfate transporters from tomato induced by low sulfate and infection by the vascular pathogen Verticillium dahliae - Jonathan R. Howarth; Pierre Fourcroy; Jean-Claude Davidian; Frank W. Smith; Malcolm J. Hawkesford (Planta, 2003)

Sulfate inhibition of molybdenum-dependent nitrogen fixation by planktonic cyanobacteria under seawater conditions: a non-reversible effect - Roxanne Marino; Robert W. Howarth; Francis Chan; Jonathan J. Cole; Gene E. Likens (Hydrobiologia, 2003)

Quantitative trait loci associated with traits determining grain and stover yield in pearl millet under terminal drought-stress conditions - R. S. Yadav; C. T. Hash; F. R. Bidinger; G. P. Cavan; C. J. Howarth (Theoretical and Applied Genetics, 2002)

A History of Regression and Related Model-Fitting in the Earth Sciences (1636?-2000) - Richard J. Howarth (Natural Resources Research, 2001)

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews‐Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)
The introduction of alien, or nonindigenous, animals and plants has been identified by scientists and policy makers as a major threat to biodiversity in marine ecosystems. Although government agencies have struggled to control alien species on land and freshwater for decades with mixed success, the control of alien marine species is in its infancy. Prevention of introduction and establishment must be the first priority, but many populations of alien marine species are already well established worldwide. National and international policies leave loopholes for additional invasions to occur and provide only general guidance on how to control alien species once they are established. To address this issue, a multinational group of 25 scientists and attorneys convened in 1998 to examine options for controlling established populations of alien marine species. The discussions resulted in a framework for control of alien marine species to provide decision‐making guidance to policymakers, managers, scientists, and other stakeholders. The framework consists of seven basic steps: (1) establish the nature and magnitude of the problem, (2) set objectives, (3) consider the full range of alternatives, (4) determine risk, (5) reduce risk, (6) assess benefits versus risks, and ( 7) monitor the situation. This framework can provide guidance for control efforts under the existing patchwork of national laws and can help provide a foundation for international cooperation.

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews-Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)

Rapid Communication: Climatic Control on Eutrophication of the Hudson River Estuary - Robert W. Howarth; Dennis P. Swaney; Thomas J. Butler; Roxanne Marino (Ecosystems, 2000)

A novel approach for estimating ecosystem production and respiration in estuaries: Application to the oligohaline and mesohaline Hudson River - Dennis P. Swaney; Robert W. Howarth; Thomas J. Butler (Limnology and Oceanography, 1999)
Most estimates of metabolism in estuaries are based on water samples incubated in bottles. Such approaches may severely underestimate rates of both gross primary production (GPP) and respiration for a variety of reasons, including reduced turbulence, unnatural light fields, respiration of 14 C‐labeled organic matter, and altered grazer communities. These problems may be particularly intense in turbid and deeply mixed estuaries. The measurement of metabolism from in situ changes in dissolved oxygen (DO) concentration over a diel time period offers a potential solution to these problems, but complicated patterns of water advection and mixing in estuaries have limited the use of such open‐water approaches. Here, we describe a method of using diel changes in oxygen concentrations in the oligohaline and mesohaline Hudson River estuary to estimate GPP, whole‐ecosystem respiration (ER), and net ecosystem production (NEP). For this approach, concentrations of DO at any given time for several stations are described as a function of salinity and depth, providing a surface in the three‐dimensional space of oxygen, depth, and salinity. The change in this “response surface” for oxygen over time, once corrected for atmospheric exchange, allows the estimation of metabolism rates. The regression procedures used allow an estimate of the standard error associated with the metabolism measures. For the mesohaline Hudson River estuary, these standard errors are reasonably small. Similarly, any potential errors associated with the estimation of atmospheric exchange in oxygen are small for the Hudson. The technique should be useful for estimating GPP, NEP, and ER in other partially mixed estuaries without the biases associated with incubations in bottles.

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Soil-plant interactions in a neotropical mangrove forest: iron, phosphorus and sulfur dynamics - Ruth E. Sherman; Timothy J. Fahey; Robert W. Howarth (Oecologia, 1998)

Internal free magnesium modulates the voltage dependence of contraction and Ca transient in rabbit ventricular myocytes - F. C. Howarth; Allan J. Levi (Pflügers Archiv - European Journal of Physiology, 1998)

”Voltage-activated Ca release" in rabbit, rat and guinea-pig cardiac myocytes, and modulation by internal cAMP - Ion A. Hobai; F. Chris Howarth; Vijay K. Pabbathi; Geoff R. Dalton; Jules C. Hancox; Jie-Quan Zhu; Susan E. Howlett; Gregory R. Ferrier; A. J. Levi (Pflügers Archiv - European Journal of Physiology, 1997)

Dietary and physiological studies to investigate the relationship between calcium and magnesium signalling in the mammalian myocardium - Jaipaul Singh; Brenda I. Hustler; John J. Waring; Frank C. Howarth (Molecular and Cellular Biochemistry, 1997)